X-ray translucent reaction cell for simulation of carbon mineral storage reservoir environments - Ian D. Watt; Ian B. Butler; James Gilgannon; Lucas Martins; Florian Fusseis; R. Stuart Haszeldine; Ian Molnar; Stuart M.V. Gilfillan (International Journal of Greenhouse Gas Control, 2024)

Contrasting Futures for Australia’s Fisheries Stocks Under IPCC RCP8.5 Emissions – A Multi-Ecosystem Model Approach - Heidi R. Pethybridge; Elizabeth A. Fulton; Alistair J. Hobday; Julia Blanchard; Catherine M. Bulman; Ian R. Butler; William W. L. Cheung; Leo X. C. Dutra; Rebecca Gorton; Trevor Hutton; Richard Matear; Hector Lozano-Montes; et al. (Frontiers in Marine Science, 2020)

Mesolithic human occupation and seasonality: sclerochronology, δ18O isotope geochemistry, and diagenesis verification by Raman and LA-ICP-MS analysis of Argyrosomus regius (meagre) sagittae otoliths from layer 1 of Cabeço da Amoreira Mesolithic shell midden (Muge, Portugal) - Rita Dias; Juan Estrella-Martínez; Paul Butler; Alexandra Nederbragt; Ian R. Hall; Pedro Barrulas; Anne France Maurer; Ana Mafalda Cardeira; José Mirão; Cleia Detry; Nuno Bicho (Archaeological and Anthropological Sciences, 2019)

Mobilization of horizontally acquired island 2 is induced in planta in the phytopathogen P ectobacterium atrosepticum SCRI 1043 and involves the putative relaxase ECA 0613 and quorum sensing - Bhanupratap R. Vanga; Pavithra Ramakrishnan; Ruth C. Butler; Ian K. Toth; Clive W. Ronson; Jeanne M. E. Jacobs; Andrew R. Pitman (Environmental Microbiology, 2015)
Summary Integrative and conjugative elements ( ICEs ) contribute to the rapid evolution of bacterial pathogens via horizontal gene transfer of virulence determinants. ICEs have common mechanisms for transmission, yet the cues triggering this process under natural environmental or physiological conditions are largely unknown. In this study, mobilization of the putative ICE horizontally acquired island 2 ( HAI 2), present in the chromosome of the phytopathogen P ectobacterium atrosepticum SCRI 1043, was examined during infection of the host plant potato. Under these conditions, mobilization of HAI 2 increased markedly compared with in vitro cultures. In planta ‐induced mobilization of HAI 2 was regulated by quorum sensing and involved the putative ICE ‐encoded relaxase ECA 0613. Disruption of ECA 0613 also reduced transcription of genes involved in production of coronafacic acid (Cfa), the major virulence factor harboured on HAI 2, whereas their expression was unaffected in the quorum‐sensing ( expI ) mutant. Thus, suppression of cfa gene expression was not regulated by the mobilization of the ICE per se , but was due directly to inactivation of the relaxase. The identification of genetic factors associated solely with in planta mobilization of an ICE demonstrates that this process is highly adapted to the natural environment of the bacterial host and can influence the expression of virulence determinants.